Ринок зерна в Україні як складова міжнародної макроекономіки, міжнародної торгівлі та оцінки кон’юнктури світових ринків - Решитько, Т. В.; Насипайко, Д. С.; Reshytko, T.; Nasypaiko, D. (ЦНТУ, 2025)
Метою статті є дослідження проблем розвитку ринку зерна в Україні на сучасному етапі як невід`ємної складової міжнародної макроекономіки, показ його особливостей та ролі у міжнародній торгівлі й при оцінці кон’юнктури світових ринків, окреслення перспектив його подальшого функціонування. Зазначено, що зерно займає провідне місце у структурі аграрної продукції, яка вирішує питання продовольчої безпеки держави та кон’юнктури світових ринків тощо. The purpose of the article is to study the problems of the development of the grain market in Ukraine at the present stage as an integral component of international macroeconomics, to show its features and role in international trade and in assessing the situation on world markets, and to outline the prospects for its further functioning. It has been noted that grain occupies a leading place in the structure of agricultural products, which solves the issues of food security of the state and the situation on world markets etc.
The Grain Market in Ukraine as a Component of International Macroeconomics, International Trade and Assessment of the Situation in World Markets
Keywords: ринок зерна; міжнародна макроекономіка; міжнародна торгівля; кон’юнктура світових ринків; grain market; international macroeconomics; international trade; world market conditions